Advances in Elastomers - Sedlačík, Michal (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Elastomer materials are characterized by their high elongation and (entropy) elasticity, which makes them indispensable for widespread applications in various engineering and medical areas as well as consumer goods. This book focuses on the state-of-the-art of elastomers covering all aspects from their properties to applications. The development and testing of advanced elastomers is of particular interest. Attention is given to various aspects of elastomers, such as ever-increasing environmental concepts dealing with recyclability and reusability, incorporation of functional groups or additives to obtain novel functionality or bioelastomers, analytical description of mechanisms and structure relations of the fracture behavior of elastomers, and their external stimuli-responsive character. The scope of the book encompasses contributions at the frontier of science in polymer network synthesis, experimental and theoretical physics of polymer networks, and new structures and functionalities incorporated into elastomers leading to enhanced properties of crosslinked elastomeric materials, among others.